New micro-solid phase extraction techniques based on mesoporous materials for selected antibiotic and antifungal agents - Yahaya, Noorfatimah (2014)
New microextraction techniques have been developed for sample preparation of azole drugs and penicillins in water, milk and biological samples prior to their liquid chromatographic determination. A microextraction method based on solid phase membrane tip extraction (SPMTE) incorporated with mesoporous silica, MCM-41, was developed for the determination of azole antifungal drugs, namely voriconazole (VRZ), ketoconazole (KTZ) and itraconazole (ITZ) in human plasma. Under the optimized conditions, the method demonstrated good linearity (r2 = 0.9958) over a concentration range of 60 - 8000 µg L-1 with low limits of detection in the range of 20 - 40 µg L-1. MCM-41-SPMTE required only minute amounts of adsorbent (3 mg) and desorption solvent (100 µL) and proved a successful extraction technique with high relative recoveries in the range of 82.5 - 111.0% for the analytes. MCM-41 was also employed as adsorbent in dispersive micro-solid phase extraction (D-µ-SPE) of six azole antifungal drugs including VRZ, KTZ, miconazole (MCZ), clotrimazole (CTZ), fluconazole (FLZ) and econazole (ECZ). The optimized D-µ- SPE was successfully applied to the determination of azole drugs in urine and human plasma. The method showed good linearity (r2 = 0.9900) over a concentration range of 0.1 - 10000 µg L-1, excellent limits of detection in the range of 0.001 - 1.500 µg L-1 and good relative recoveries in the range of 80.9 - 116.8%. A D-µ-SPE method incorporating new mesoporous carbon COU-2 as adsorbent was developed for the determination of three penicillins in water and milk samples. Under the optimized conditions, COU-2-D-µ-SPE showed excellent limits of detection in the range of 0.06 - 3.3 µg L-1 for oxacillin, cloxacillin and dicloxacillin with good linearity (r2 = 0.9992) in the concentration range of 0.1 - 5000 µg L-1 and good relative recoveries (80.3 - 113.6%). COU-2-D-µ-SPE is beneficial in terms of solvent saving, simplified analytical procedure and rapid extraction. The surface of COU-2 was further modified by functionalization with vinyl group to improve the extraction of target azole antifungal drugs by increasing the hydrophobicity of the adsorbent. Vinyl-COU-2 was used as adsorbent in D-µ-SPE (Vinyl-COU-2-D-µ-SPE) for the determination of azole antifungal drugs in water and biological samples. Excellent limits of detection (0.4 - 1.6 µg L-1) were obtained for KTZ and ITZ, respectively, with good linearity (r2 = 0.9959) in the concentration range of 1 - 400 µg L-1. The method provided high enrichment factors up to 92 with excellent relative recoveries in the range of 89.8 - 113.9% for both analytes. The developed microextraction techniques combined with liquid chromatography have proved to be simple, rapid and efficient with performances that are superior to those of conventional methods and suitable for the determination of azole drugs and penicillins in water, milk and biological samples.